Prospective analysis of factors precluding the initiation of durvalumab from an interim analysis of a phase II trial of S-1 and cisplatin with concurrent thoracic radiotherapy followed by durvalumab for unresectable, locally advanced non-small cell lung cancer in Japan (SAMURAI study). (July 2022) - Tanzawa, Shigeru; Makiguchi, Tomonori; Tasaka, Sadatomo; Inaba, Megumi; Ochiai, Ryosuke; Nakamura, Junya; Inoue, Koji; Kishikawa, Takayuki; Nakashima, Masanao; Fujiwara, Keiichi; Kohyama, Tadashi; Ishida, Hiroo; et al.
Background: The standard of care for unresectable, locally advanced non-small cell lung cancer (LA-NSCLC) is chemoradiotherapy (CRT) followed by durvalumab, based on the PACIFIC trial. Disease progression and pneumonitis were reported as the main reasons to preclude the initiation of durvalumab in multiple retrospective studies. However, the transition rate and the reasons for failure to proceed to consolidation therapy with durvalumab after CRT were not evaluated prospectively. Although phase II studies in Japan have shown high efficacy and tolerability of CRT with cisplatin + S-1 (SP), no prospective study using durvalumab after SP-based CRT has yet been reported. We therefore conducted a phase II study to verify the efficacy and safety of durvalumab following SP-based CRT. In this interim analysis, we report the transition rate and the reasons for its failure. Methods: In treatment-naïve LA-NSCLC, cisplatin (60 mg/m 2, day 1) and S-1 (80–120 mg/body, days 1–14) were administered with two 4-week cycles with concurrent thoracic radiotherapy (60 Gy) followed by durvalumab every 2 weeks for up to 12 months. The primary endpoint was 12 month progression-free survival rate. Results: Fifty-nine patients were enrolled, of whom 86.4% (51/59) proceeded to durvalumab. All of them initiated durvalumab within 42 days after CRT [median 18 days (range: 3–38)], including 27.5% (14/51) in <14 days. Common reasons for failure to proceed to durvalumab were disease progression (2/59, 3.4%) and adverse events (6/59, 10.2%). Among the latter cases, four resumed treatment and proceeded to durvalumab within 42 days on off-protocol. The objective response rate and the disease control rate were 62.7% and 93.2%, respectively. The incidences of ⩾grade 3 pneumonitis, febrile neutropenia, and esophagitis were 0%, 8.5%, and 3.4%, respectively. Conclusion: Regarding durvalumab after CRT, this interim analysis of the SAMURAI study clarified the high transition rate, early introduction, and reasons for failure to proceed to consolidation therapy, which were not determined in the PACIFIC trial. Trial registration: Japan Registry of Clinical Trials, jRCTs031190127, registered 1 November, 2019, https://jrct.niph.go.jp/latest-detail/jRCTs031190127 .